FORMAT AND CONTENT OF PRIMARY CURRICULUM IN THE UNITED KINGDOM OF GREAT BRITAIN AND NORTHERN IRELAND COMPARATIVE ANALYSES - Iryna Borysenko; Oksana Bykonia; Tetiana Ihnatovych (Pavlo Tychyna Uman State Pedagogical University, 2019)
Current reforms in education system in all European countries involve modernization of the education content in terms of implementation of new educational standards, programmes of study and textbooks, refining teaching approaches. It actualizes comparative studies in order to outline achievements of European education and to define opportunities to use them in an innovative and efficient way in Ukrainian education. The study aims to make comparative analyses of curriculum format and in four parts of the UK in order to outline areas of similarities and differences of the curriculum content in the UK. The study covers approaches to designing of school curriculum in terms of programmes of study formulation (in accordance with national curriculum aims, community, school and pupils needs); planning a timetable; the number of terms in a year; lesson length, subject allocations, minimum time per subject per week, pupil groupings, additional hours for numeracy and literacy. The article illustrates how the schools are adapting their curriculum in the light of current curriculum and education reforms. The article draws on evidence from a sample of primary schools in the UK, which provides an overview of how primary schools currently build, plan, implement, monitor and improve their curriculum. Key approaches to designing and structuring the curriculum content are also specifies in the study/ These are the principle of considering community and pupils' needs, educational traditions while forming the education content, practice-centered approach, resulting quality and the principle of flexibility.